Human resources for health in Peru: Recent trends (2007-2013) in the labour market for physicians, nurses and midwives - Jimenez M.M. (2017)
Most analyses of gaps in human resources for health (HRH) do not consider training and the transition of graduates into the labour market. This study aims to explore the labour market for Peru’s recent medical, nursing, and midwifery graduates as well as their transition into employment in the Ministry of Health’s (MOH) system.